ЎЗБЕКИСТОНДА ТАЪЛИМ ТИЗИМИНИНГ ТАРАҚҚИЁТИ ВА САМАРАДОРЛИГИ (Scientific journal of the Fergana State University, 2023)
Questions connected with reforms which are realized in sphere of education, their evolutionary development, its lawful foundations, government’s attention to this sphere, international collaboration, and achieved successes are analyzed in the article.